Diventare grandi con il «Pioniere» (1950-1962) - Silvia, Franchini (Firenze University Press, 2006)
The conception and creation of the children's magazine "Pioniere" was an integral part of the extensive educational plan implemented by the PCI in the fifties for the construction of a new society. This book studies the issue of the dialogue set up with the young readers which evolved through a series of innovative initiatives, but was nourished above all by the post column run by the editor Dina Rinaldi. This was pivotal in the "education of feelings" and destined, in the optic of the "Pioniere", to the training up of the new generations.